Improving process conformance with Industry Foundation Processes (IFP). Issue 2 (April 2016) - Golzarpoor, Behrooz; Haas, Carl T.; Rayside, Derek
Abstract: Conformance with standard corporate and institutional processes and industry best practices are sought because of regulatory requirements and evidence that best practices lead to improved project performance. Automated workflow engine enabled Industry Foundation Processes (IFP) are introduced in this paper that facilitate process conformance through structural transparency, foundation process inheritance, and automated conformance checking. While IFP processes can be customized to suit particular project or corporate conditions, they need to conform to a standard core structure and thus behavior. This has been achieved through defining specific workflow inheritance rules and developing an automated structural process conformance checking algorithm. The algorithm has been developed based on graph theory fundamentals using a first-order logic language, which compares two workflows and detects the conformance of a customized one with its associated IFP. The developed algorithm has been functionally tested and validated with different structural settings of workflows with a number of critical cases. Its functionality has been demonstrated in this paper with an example of the commonly used process of RFI (Request for Information). A new construct is thus contributed that can help improve process conformance to industry best practices particularly in the architectural, engineering, and construction industry, leading to improved project conformance.